2022
DOI: 10.1186/s12859-022-04917-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CRS-associated cytokines in CAR-T therapy with meta-GNN and pathway crosstalk

Abstract: Background Chimeric antigen receptor T-cell (CAR-T) therapy is a new and efficient cellular immunotherapy. The therapy shows significant efficacy, but also has serious side effects, collectively known as cytokine release syndrome (CRS). At present, some CRS-related cytokines and their roles in CAR-T therapy have been confirmed by experimental studies. However, the mechanism of CRS remains to be fully understood. Methods Based on big data for human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…On that basis, this study incorporates a dataset comprising 1615 cytokines and proteins. The prediction results exhibit varying probabilities of being linked to CRS [ 22 ]. To facilitate the model’s assessment on the biological dataset, a total of 200 cytokines and proteins were selected from both ends of the Meta-GNN probabilistic sequencing results to predict CRS-related cytokines for classification testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On that basis, this study incorporates a dataset comprising 1615 cytokines and proteins. The prediction results exhibit varying probabilities of being linked to CRS [ 22 ]. To facilitate the model’s assessment on the biological dataset, a total of 200 cytokines and proteins were selected from both ends of the Meta-GNN probabilistic sequencing results to predict CRS-related cytokines for classification testing.…”
Section: Methodsmentioning
confidence: 99%
“…The comparison between the predictions of the Meta-DHGNN and Meta-GNN [ 22 ] is shown in Figure 6 , showing that 74 cytokines are in common and 62 are unique upon a more accurate cytokine interaction network.…”
Section: Methodsmentioning
confidence: 99%
“…The migration and infiltration into tumor tissue are the main obstacles of CAR T efficiency in solid tumors (128) but also play an important role in hematologic malignancies (81, 97). Adequate expression of adhesion molecules (e.g., LFA-1, VCAM-1, ICAM-1, VEGFA, and others), chemokines (e.g., CCL3, CCL4, CXCL9, CXCL10, CXCL11, CXCL12, and others), and other guidance molecules are of paramount importance for effective CAR T cell homing (96,(129)(130)(131)(132)(133)(134)(135). Therefore, inadequate expression of these navigation-related molecules could serve as a negative predictive factor for the progression and outcome of CAR T cell therapy (96,131,132).…”
Section: Markers Of the Immune Systemmentioning
confidence: 99%
“…As a result of the high production of cytokines during CAR-T cells therapy, CRS is the most common SAEs of immune system ( 28 ). It was found that 128 cytokines may be closely related to CRS, among which IL6, IFN-γ, TNF-α, ICAM-1, VCAM-1, VEGFA and other important factors may be the key factors to predict CRS ( 29 ). Additionally, it causes SAEs throughout the body in a variety of systems ( 30 ).…”
Section: Clinical Presentation Of Saes Associated With Car-t Cells Th...mentioning
confidence: 99%